Lifestyles related to alcohol consumption, drugs and gambling ... - Anctil, Mélanie; Chevalier, Serge; Cree Board Of Health And Social Services Of James Bay; Institut National De Santé Publique Du Québec (Cree Board of Health and Social Services of James Bay & Institut national de santé publique du Québec, 2008)
25 p. : ill. 28 cm. "Reproduction for non-commercial purposes is permitted, as long as the source is acknowledged." ... : This publication presents the findings of a health survey carried out in 2003 among households of Iiyiyiu Aschii. A similar survey had been undertaken in the region by Santé Québec in 1991 (Santé Québec, 1994). Ten years later, the Public Health Department of the Cree Board of Health and Social Services of James Bay (CBHSSJB) urgently required a new picture of its population’s state of health. The purpose of the 2003 survey was to gather up-to-date information on the region’s main health problems and related factors in order to improve the planning, administration, and evaluation of various social and health programs. ...